Historical background of Lima's urban development - Ìsmodes Alegría, Julio César (2012)
This research summary has been developed according to the guidelines established by the Institute of Economic and Social Research (IECOS) of the FIECS UNI and aims to describe in summary form the background and most relevant aspects of the process of urban development of the city of Lima, emphasizing them for the period between the end of the 19th century and the beginning of the 20th century, during which the most important changes registered by the capital of the country took place, in its transition from a colonial city to a modern Lima that appeared in the first decades of the last century and laid the foundations for the subsequent urban growth of the city.